Incomplete Contracts and Investment : A Study of Land Tenancy in Pakistan - Jacoby, Hanan G. (World Bank, Washington, DC, 2012)
When contracts are incomplete, relationship-specific investments may be underprovided due to the threat of opportunistic expropriation or holdup. The authors find evidence of such underinvestment on tenanted land in rural Pakistan. Using data from households cultivating multiple plots under different tenure arrangements, they show that land-specific investment is lower on leased plots. This result is robust to the possible effects of asymmetric information in the leasing market. Greater tenure security also increases land-specific investment on leased plots. Moreover, variation in tenure security appears to be driven largely by heterogeneity across landlords, suggesting that reputation may be important in mitigating the holdup problem.